2020
DOI: 10.1371/journal.pone.0228747
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of S-alk(en)yl-L-cysteine sulfoxide lyase isoform genes and determination of allicin contents in Allium species

Abstract: Alliinase is the key enzyme in allicin biosynthesis pathway. In the current study, the identification and sequencing of alliinase genes along with determination of allicin contents were reported for Allium species with a novel report for Iranian endemic species. The presence of different isoforms in the Allium being discovered for the first time. In bulbs tissue, the highest allicin concentration was in Allium sativum, A. umbilicatum, and A. fistolosum (1.185%, 0.367%, and 0.34%, respectively), followed by A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Among Allium species, organic sulfur synthesis has a similar pathway, but secondary metabolite biosynthesis and accumulation are related to regulator genes with tissue-specific expression patterns, which highly affect the quantities and chemical compositions in each Allium species 21 . Given this, RNA-seq has been applied effectively to discover genes related to sulfur metabolism in some Allium species such as A. cepa 14 , 22 , 23 , A. sativum 12 , 24 , and Allium fistulosum 25 . So, the transcriptome analysis in another species allows us to provide a more in-depth exploration of various aspects of the sulfur pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among Allium species, organic sulfur synthesis has a similar pathway, but secondary metabolite biosynthesis and accumulation are related to regulator genes with tissue-specific expression patterns, which highly affect the quantities and chemical compositions in each Allium species 21 . Given this, RNA-seq has been applied effectively to discover genes related to sulfur metabolism in some Allium species such as A. cepa 14 , 22 , 23 , A. sativum 12 , 24 , and Allium fistulosum 25 . So, the transcriptome analysis in another species allows us to provide a more in-depth exploration of various aspects of the sulfur pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Functional transcriptome analysis revealed 11 alliinase transcripts belonging to four distinct genes expressed in all three tissues with a different pattern. It has been previously detected and demonstrated 14 that the isoforms expression pattern of alliinase gene is variable among different tissues of various Allium species. Previous studies 14 , 44 have also described the presence of nonhomologous alliinase genes in different tissues of A llium species, which is consistent with the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garlic ( Allium sativum ), leeks ( Allium porrum ), and onion ( Allium cepa ) are examples of the alliin–alliinase pathway [ 21 ]. These two pathways are evolved in herbivore defense and avoid pathogenic attack [ 28 ]. Table 2 represents examples of various sulfur-containing secondary metabolites.…”
Section: Major Plant Secondary Metabolites Involved In Biotic Stress ...mentioning
confidence: 99%
“…Since the enzymatic reaction of the alliinase produces the bioactive compound in garlic, the studies analyzed the genetic profile of the gene. These studies revealed the existence of multiple variations i.e., insertion/ deletion in the exonic and intronic regions which play the significant role in differential expression of the alliinase gene hence responsible for the allicin content in individual garlic genotypes (Ovesná et al, 2015;Sayadi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%